Analisis Antalgin dalam Jamu Pegal Linu yang Dijual di Pasar Beringharjo Yogyakarta - Siti Fatimah; Muji Rahayu; Debi Firma Indari (LPPM STIKES Guna Bangsa, 2017)
Background: Traditional medicine is an ingredient or ingredients in the form of plant material, animal material, mineral materials, preparation essence (galenic), or mixtures of these materials that have historically been used for treatment, and can be applied according to the prevailing norms in society. Traditional medicine is often chosen as a remedy for health care is herbal, because herbal medicine is a health drink. Chemicals drugs were added by the makers of herbal medicine with the intent may be to increase the efficacy of herbal medicine and herbal medicine provide more instant effect, it is becoming a source of danger herbs. BPOM many find herbs aching pains who defiled chemical medicines like phenylbutazone, methampyrone, diclofenac sodium, piroxicam, paracetamol, prednisone, or dexamethasone. Chemicals a drug it is set in PERMENKES 007 of 2012. Methods: This research is to describe the whether or not of chemicals in the antalgin sold in the Beringharjo traditional market Yogyakarta. The method used to test the lab using thin layer chromatography. Research data presented in terms of percent. Results: Research is obtained value Rf sample 0.63 until 0.8 one sampel having the value Rf and fluorescence equal to standard methampyrone. Value Rf standard methampyrone 0,78 and red purple fluorescence. Conclusion: There are methampyrone in herbal medicine aching pains sold in the Beringharjo traditional market to a presentation positive results as many 8.3% and negative results 91.7%.